1976
DOI: 10.3109/00498257609151671
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal Styrene Mono-oxygenase and Styrene Epoxide Hydrase Activities in Rats

Abstract: 1. Styrene epoxide formation and styrene epoxide hydration have been studied in liver, lung, kidney, heart, spleen and brain of female and male rats. 2. Styrene epoxide formation is NADPH-dependent although it is enhanced when NADH is added together with NADP. This enzymic activity is inhibited by metyrapone and SKF 525-A but not by the effective inhibitors of epoxide hydrase, 1,2-epoxy-3,3,3-trichloropropene and cyclohexene oxide. 3. Known inducers of liver microsomal mono-oxygenases show a different activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…As already proved for several other related compound~ (Salmona et al 1976;Malvoisin et al 1979;Gervasi et a/ 1982;Bolt et al 1983;Del Monte et al 1985), the epoxi&-tion of MP is also catalyzed by cytochrome P-450 depeadent mono-oxygenases. This conclusion is drawn from the observation that NADPH is required for the formation of MEP and that the epoxidation of MP is inducible bl phenobarbital, a known inductor of the mono-oxygenases The latter results are in agreement with the data previousl) published for 1,3-butadiene (Malvoisin et al 1979) Moreover, CO, metyrapone and SKF 525-A, well-know~ inhibitors of the cytochrome P-450 dependent mono-oxy genases (Testa et al 1981), all inhibit the biotransforrm.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…As already proved for several other related compound~ (Salmona et al 1976;Malvoisin et al 1979;Gervasi et a/ 1982;Bolt et al 1983;Del Monte et al 1985), the epoxi&-tion of MP is also catalyzed by cytochrome P-450 depeadent mono-oxygenases. This conclusion is drawn from the observation that NADPH is required for the formation of MEP and that the epoxidation of MP is inducible bl phenobarbital, a known inductor of the mono-oxygenases The latter results are in agreement with the data previousl) published for 1,3-butadiene (Malvoisin et al 1979) Moreover, CO, metyrapone and SKF 525-A, well-know~ inhibitors of the cytochrome P-450 dependent mono-oxy genases (Testa et al 1981), all inhibit the biotransforrm.…”
Section: Discussionmentioning
confidence: 84%
“…It has already been demonstrated that several important industrial chemicals such as 1,3-butadiene, cyclohexadiene, styrene and isoprene are metabolized to epoxides (Salmona et al 1976;Watabe et al 1978;Malvoisin et al 1979;Gervasi et al 1982;Malvoisin and Roberfroid 1982;Bolt et al 1983;Del Monte et al 1985). Certain of these seemed to be mutagenic, but it is clear that the adverse properties of 264 some arene and alkene oxides can not be simply extrapolated to epoxides in general (Oesch 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Styrene is also metabolized by eukaryotes [69][70][71]. In mammals, styrene metabolism serves primarily to counteract the toxic effects of styrene [71], whereas a few fungal strains can utilize the compound as carbon source for growth [70].…”
Section: Styrene Epoxidasementioning
confidence: 99%
“…The toxicity of styrene and its metabolite epoxystyrene in humans, combined with its widespread use as a precursor in the manufacturing of polymers, has spurred efforts to utilize bacterial and fungal cells for bioremediation. Even though the first step of styrene metabolism in eukaryotes is also the formation of the epoxide, fungal and mammalian cells employ cytochrome P450 monooxygenases (Section 10.2.1) to catalyze this reaction [69,72]. It is quite remarkable but not uncommon to find that the same chemical transformation can be achieved by different mechanisms.…”
Section: Styrene Epoxidasementioning
confidence: 99%
“…This system is of interest because it is involved in the metabolism of episodes that are postulated to be reactive metabolites of steroid contraceptives. Salmona et al 20 found that a contraceptive steroid combination, lynestrenol plus mestranol, stimulated styrene monooxygenase and inhibited styrene epoxide hydrase -both processes allowing levels of epoxide to increase. However, in a subsequent paper, Jori et al 21 found that lynestrenol plus mestranol stimulated both epoxide monooxygenase and epoxide hydrase, as did norethisterone plus mestranol.…”
Section: Experimental Observationsmentioning
confidence: 99%